Analysis of Factors Affecting Human Resource Performance at Martha Friska Multatuli General Hospital Medan - Nasution, Sri Lestari Ramadhani; Akbarinda, Zsizsi; Girsang, Ermi (Newinera Publisher, 2024)
In an effort to improve the degree of public health, human resources are needed who have the capacity, competence and professionalism in their fields so that they are able to apply the knowledge and knowledge they have in health services to the community. Without competence supported by reliable human resources, a hospital will have difficulty competing with other hospitals. To improve HR performance, it is necessary to pay attention to satisfaction factors at work. To know and analyze the influence of leadership style, work motivation, work quality, quantity of work, punctuality, work effectiveness, independence and work commitment on HR performance. is a descriptive research with a quantitative analytical approach. The population in this study was all human resources at RSU Martha Friska Multatuli Medan totaling 231 people, the sample of this study was 231 using total sampling techniques. of the study using the chi square statistical test obtained results: leadership style (p = 0.000), work motivation (p = 0.027), work quality (p = 0.000), work quantity (p = 0.000), punctuality (p = 0.00), work effectiveness (p = 0.000), independence (p = 0.000), work commitment (p = 0.000). Which shows the influence of HR performance of RSU Martha Friska Medan, and by using multiple logistic regression, the most dominant variable is work commitment, this can be seen from the Exp (B) value of 6,067 (which means that work commitment has 6 times more influence on the performance of human resources at RSU Martha Friska Multatuli Medan.